Synthesis, structural and electrical properties of triethylene glycol (TREG) stabilized Mn0.2Co0.8Fe2O4 NPs - Deligoz, H.; Baykal, A.; Tanriverdi, E. E.; Durmus, ZEHRA; Toprak, M. S. (My University, 2012)
Triethylene glycol (TREG) stabilized Mn0.2Co0.8Fe2O4 NPs was synthesized by a glycothermal reaction. XRD analysis identified the product as Mn0.2Co0.8Fe2O4 with a high phase purity. Nano-sized particles with an average size of about 6-8 nm were obtained with nearly single crystalline nature with TEM analysis. Superparamagnetic-like behavior of TREG stabilized Mn0.2Co0.8Fe2O4 NPs was observed by VSM. The binding between TREG and Mn0.2Co0.8Fe2O4 NPs was investigated with FT-IR and found to be via O on the TREG and NP surface. TG analysis indicated that the Mn0.2Co0.8Fe2O4 NP content was about 40%, with a TREG-shell content to be around 60%. Overall conductivity of the nanocomposite is in the range of 10(-10) to 10(-7) S cm(-1) with a strong dependence on temperature and frequency, indicating ionic conductivity. The nanocomposite exhibited lower epsilon- and epsilon - compared to TREG stabilized Mn0.2Co0.8Fe2O4 NPs due to the doping of co-doping of manganese and cobalt. (C) 2012 Elsevier Ltd. All rights reserved.